Morphology of three polycentric rumen fungi and description of a procedure for the induction of zoosporogenesis and release of zoospores in cultures - Ho, Y. W.; Bauchop, T. (Springer, 1991)
Three polycentric rumen fungi, LL, LC2 and Ruminomyces elegans (C2), isolated from the rumen of cattle were grown in six culture media. LL and LC2 were morphologically similar. Their characteristics resembled those of Orpinomyces and Neocallimastix joyonii, and they grew well and produced sporangia after 3-4 d growth in all the media. R. elegans differed morphologically from LL and LC2, but although it also grew well in all media, abundant sporangia occurred only after 2-3 d growth in media containing cellulose. Undifferentiated sporangia were produced by all three isolates; differentiation of the sporangia did not occur in the spent growth media. However, if thalli possessing recently-formed sporangia were transferred to, or flooded with, fresh liquid medium or rumen fluid, zoosporogenesis and liberation of zoospores occurred within 17-20 min for isolates LL and LC2 and 30 min for R. elegans. Procedures for inducing zoosporogenesis by polycentric anaerobic fungi are described.